Northern Manhattan Hispanic Caregiver Intervention Effectiveness Study: protocol of a pragmatic randomised trial comparing the effectiveness of two established interventions for informal caregivers of persons with dementia. Issue 11 (25th November 2016) - Luchsinger, José A; Burgio, Louis; Mittelman, Mary; Dunner, Ilana; Levine, Jed A; Kong, Jian; Silver, Stephanie; Ramirez, Mildred; Teresi, Jeanne A
Abstract : Introduction: The prevalence of dementia is increasing without a known cure, resulting in an increasing number of informal caregivers. Caring for a person with dementia results in increased stress and depressive symptoms. There are several behavioural interventions designed to alleviate stress and depressive symptoms in caregivers of persons with dementia with evidence of efficacy. Two of the best-known interventions are the New York University Caregiver Intervention (NYUCI) and the Resources for Enhancing Alzheimer's Caregivers Health (REACH). The effectiveness of the NYUCI and REACH has never been compared. There is also a paucity of data on which interventions are more effective in Hispanics in New York City. Thus, we proposed the Northern Manhattan Hispanic Caregiver intervention Effectiveness Study (NHiCE), a pragmatic clinical trial designed to compare the effectiveness of adaptations of the NYUCI and the REACH in informal Hispanic caregivers of persons with dementia in New York City. Methods and analysis: NHiCE is a 6-month randomised controlled trial comparing the effectiveness of adaptations of the NYUCI and REACH among 200 Hispanic informal adult caregivers of persons with dementia. The planned number of sessions of the NYUCI and REACH are similar. The primary outcome measures are changes from baseline to 6 months in the Zarit Caregiver Burden Scale and Geriatric Depression Scale. Our primary approach to analyses will be intent-to-treat. The primary analyses will use mixed random effects models, and a full information maximum likelihood approach, with sensitivity analyses using generalised estimating equation. Ethics and dissemination: NHiCE is approved by the Institutional Review Board of Columbia University Medical Center (protocol AAAM5150). A Data Safety Monitoring Board monitors the progress of the study. Dissemination will include reports of the characteristics of the study participants, as well as a report of the results of the clinical trial. Trial registration number: NCT02092987, Pre-results.